Universal Signal Conditioning Technique for Fiber Bragg Grating Sensors in PLC and SCADA Applications - Gary Allwood; Graham Wild; Steven Hinckley (Instruments, 2017)
Optical fibre sensors, such as Fibre Bragg Gratings (FBGs), are growing in their utilisation, although very niche in their applications. To enable a more diverse range of end users, expensive application-specific optical fibre interrogation hardware needs to be made compatible with and, ideally, easily incorporated into existing instrumentation and measurement hardware. The Programmable Logic Controller (PLC) is an ideal example of hardware used for data acquisition in many industries. As such, a module that can be connected into an existing PLC slot to collect data from electrically-neutral, EMI-immune and versatile FBG sensors is of significant advantage to the growing optical fibre sensing market. In this work, we show that both digital and analogue signals can be collected from FBG sensors and integrated seamlessly into the PLC-based control system using a transmit-reflect detection system. This technique enables fibre optic sensors to be compatible with standard industrial automation controllers in a relatively low cost and plug and play manner.